Golden Minutes: A Comprehensive Literature Review On Triage Accuracy And Response Time In Emergency Installations - Meysa Ayu Cahyani; Putri Bela Eka Safitri; Sri Rahayu; Ricky Prasetyo (Sean Institute, 2025)
The implementation of the triage system is an effective indicator in the Emergency Departement (ED) and is crucial for assessing triage accuracy, improving response time, and enhancing the quality of medical and nursing care. This study aims to find scientific evidence on the golden minutes for triage accuracy and response time in the ED. This Study üşen a literature review approach, searching for articles from several database such a PubMed, Science Direct, Garuda, and Google Scholar within the last file years 2019-2024. Analysis of eight articles revealed that the accuracy of triage performed by ED nurses ranged betwen 73%-89%, with a response time of lens than 5 minutes. Conclusion: Helathcare Professional should enhance training on triage accuracy and response time in the ED.